Experimental Investigation of Moisture Sorption Isotherms for Mefenamic Acid Tablets - Alhussaini, Maha Muhyi; Hassan, Hassanain A.; Ahmedzeki, Nada S. (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
The moisture sorption isotherms of Mefenamic acid tablets were investigated by measuring the experimental equilibrium moisture content (EMC) using the static method of saturated salt solutions at three temperatures (25, 35, and 45°C) and water activity range from 0.056 to 0.8434. The results showed that EMC increased when relative humidity increased and the sorption capacity decreased, the tablets became less hygroscopic and more stable when the temperature increased at constant water activity. The sorption curves had a sigmoid shape, type II according to Brunauer’s classification. The hysteresis effect was significant along with the whole sorption process. The results were fitted to three models: Oswin, Smith, and Guggenhein - Anderson and de Boer. According to the fitting results, the GAB model was the most appropriate model to describe the sorption behavior of Mefenamic acid; it had a regression coefficient range (0.9803-0.994), %E (0.69-4.06), and low values of SEE (0.85-2.2). The monolayer moisture content was calculated using the GAB model and it was concluded that the tablets should be stored at moisture content equal or slightly higher than (0.2046, 0.1843, and 0.1437 %) for desorption and (0.2073, 0.1269, and 0.1452 %) for adsorption for the three temperatures.